REVISION OF THE GENUS PTYCHOPHYLLOCERAS (AMMONOIDEA: PHYLLOCERATIDA) FROM THE BERRIASIAN OF THE CRIMEAN PENINSULA - Arkadiev V.V.; Bogdanova T.N. (My University, 2001)
The genus Ptychophylloceras from the Berriasian of the Crimea is revised. P. ptychoiciun (Querist.) is considered as a junior synonym off! seinistilcattim (d'Orb.). The suturai ontogeny and inner structure are studied. Three species, i.e., P. semisulcatum (d'Orb.), P. inordinatiun (Toucas), and a new species, P. teniticostatum, are described.
Keywords: Cretaceous; Berriasian; Ptychophylloceras; Crimea; Мезозой::Меловая; Мезозой::Меловая::Нижний::Берриасский; Mesozoic::Cretaceous; Mesozoic::Cretaceous::Lower::Berriasian